SYNTHESIS OF NEW DERIVATIVES OF PARAAMINOBENZENESULFACET AMIDE (Proceedings of the YSU B: Chemical and Biological Sciences, 2002)
New water-soluble derivatives of paraaminobenzenesulfacetamide have been synthesized by means of interaction of sodium derivatives of paraaminobenzene-sulfacetamide with ethylenchlorhydrine, epichlorhydrine, benzyl chloride ethyl ester of monochloracetic acid, N-P-chlorethylmorpholine, alkyl chlorides, phenylhydrazine and thiosemicarbazide. Reactions were carried out in absolute alcohol or dimethylformamide at 90–95°C and equi-molar ratio of reagents.